Religions and religiosity: the challenge to know and to recognize the other - Sonia Kramer; Joseph Edelheit (FahrenHouse, 2018)
Discourses that value religious plurality coexist in various contexts with actions of humiliation, exclusion, violence and attempts to eliminate religious groups. Committed to such questions, this text analyzes the lack of knowledge that exists about religions, even when there is coexistence between people, stands out the urgency of this recognition and discusses the role that should be exercised by the schools. The first item presents interactions between teachers and students in different institutions of Higher Education in Brazil and in the United States. These situations evidence express the difficulty of accepting the other of recognizing the religion of the other as having equal value, spirituality and relevance. The second item focuses on two philosophers whose work have an important impact in academic production, in social movements and in education conceived as community building: Martin Buber, his conception of religion and religiosity, the recognition of the other and his otherness as responsible engagement, unique ethical act; and Abraham Heschel, his vision of mankind, his passion for truth and the human search for God. The analyses of their texts invites us to bring Paulo Freire. The third item reflects on what can be done in school and specially in teacher education. And how to educate educators? How to build authentic dialogue? How to accept and educate the human being as a person (mensch), weaving the in between ourselves and others, trusting in the humanity of man, the bond and interfaith dialogue?